Trichoderma: Biology and Applications 2013
DOI: 10.1079/9781780642475.0292
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma as a human pathogen.

Abstract: This book, composed of 17 chapters, provides an update on the advances in Trichoderma research, covering most of the aspects related to the biology, genetics, genomics and applications of Trichoderma in human welfare. An introductory chapter presents an overview of Trichoderma and its applications in agriculture, industry, and in human health and the environment. Part I (chapters 2-7) focuses on Trichoderma taxonomy and physiology, specifically on molecular phylogeny, the influence of light on biology, sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Nevertheless, those authors' conclusions might have been biased, since in that study only six clinical isolates were included. More recently, several studies have emphasized the importance of this species as the causal agent of human infections (4,26,27). Three other species within the clade have been associated with human disease, i.e., T. citrinoviride, T. orientale, and T. reesei (21,27,40) The latter species has not been identified in this study, but the new species T. bissettii might be considered an opportunistic human pathogen of the Longibrachiatum clade.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Nevertheless, those authors' conclusions might have been biased, since in that study only six clinical isolates were included. More recently, several studies have emphasized the importance of this species as the causal agent of human infections (4,26,27). Three other species within the clade have been associated with human disease, i.e., T. citrinoviride, T. orientale, and T. reesei (21,27,40) The latter species has not been identified in this study, but the new species T. bissettii might be considered an opportunistic human pathogen of the Longibrachiatum clade.…”
Section: Discussionmentioning
confidence: 52%
“…DNA sequence analysis has helped clarify the taxonomy of Trichoderma, and several new species have been described based on multigene phylogenies (39,41,42). In the clinical setting, species identification has been based mainly on ribosomal DNA (rDNA) sequences (8,23,28,40), although it has been shown that the use of this locus does not provide sufficient resolution to accurately distinguish closely related species (4,26,41,43). This, together with the poor in vitro activities of commonly used antifungals against Trichoderma isolates, is an impediment for the treatment of Trichoderma infections (11,43) and limits our understanding of the epidemiology of the species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some species of this genus are clinically important (e.g. T. longibrachiatum and T. citrinoviride [13]) or harmful in the mushroom industry (e.g. T. aggressivum [16]), while others are used for the bioremediation of organic and inorganic wastes includ-Acta Biologica Hungarica 67, 2016 ribosomal fungal peptides.…”
Section: Introductionmentioning
confidence: 99%